Translation: Translator’s Note - /, Translator (Columbia Journal of Asian Law, 1988)
One of the major aims of the Journal of Chinese Law is to facilitate intellectual exchanges between Chinese and American scholars and lawyers. A prerequisite to valuable communication of this type is access by American and Chinese legal scholars to the writings of their colleagues abroad. Since 1979, there has been a remarkable expansion of legal scholarship in the People’s Republic of China (PRC), with the inauguration of scores of legal journals that present an increasingly rich abundance of legal information and theoretical debate on often controversial questions of legal theory, legislative priorities and institutional reform. Regrettably, most of this critical information is inaccessible to interested American lawyers and scholars unable to read Chinese. The Journal hopes to address this problem and promote greater understanding of Chinese legal development by publishing translations of important articles from Chinese law journals.